Catalytic spectrophotometric determination of trace Mo(vi) in milk-based beverages in the presence of bromophenol blue and H2O2 using SDS as a sensitizer. Issue 33 (4th August 2016) - Temel, Nuket Kartal; Gürkan, Ramazan
Abstract : A simple and low-cost catalytic spectrophotometric method using sodium dodecyl sulfate (SDS) as a sensitivity-improving surfactant to detect low levels of Mo(vi ) in beverage matrices was developed. Abstract : A simple and low-cost catalytic spectrophotometric method using sodium dodecyl sulfate (SDS) as a sensitivity-improving surfactant to detect low levels of Mo(vi ) in beverage matrices was developed. The method is based on the catalytic effect of molybdenum on the oxidation of 4, 4′-(1, 1-dioxido-3 H -2, 1-benzoxathiole-3, 3-diyl)bis(2, 6-dibromophenol) (bromophenol blue, HIn − ) with H2 O2 in the presence of SDS as a sensitizer in the premicellar region at pH 6.0. The surfactant-sensitive catalytic reaction was monitored by measuring the decrease in the absorbance at 590 nm after a fixed time of 5 min, which is linearly related to the molybdenum concentration in a wide working range. The optimal reaction conditions ( e.g., surfactant concentration, reagent concentration and time) were evaluated and optimized, and then the analytical figures of the merit of the method (such as the limits of detection and quantification, linear working range, accuracy and precision) were established. Linearity was observed in a Mo(vi ) ion concentration range of 5–150 μg L −1, and the limits of detection and quantification of the method were 1.80 and 5.46 μg L −1, respectively. The relative standard deviations (RSDs) and relative errors for the five replicate measurements of 25 and 100 μg L −1 Mo(vi ) were lower than 3.5% and 2.3%, respectively. The interference effect of some anions, cations and neutral species was also tested. The accuracy was controlled by the analysis of two certified samples, and the results were found statistically to be in good agreement with the certified values at a 95% confidence limit. The method was successfully applied to the catalytic determination of low levels of Mo(vi ) in milk-based beverages.